On the Strength in Weakness: Human Figures Making History - Vansover, Yaron (Journal of Interdisciplinary Studies in Education, 2019)
A good story we have read or heard weaves a web of gossamer around us,linking us to it by five emotional reactions that it arouses. Most of thesereactions are sparked by the characters in the story. To a great extent, they areresponsible for creating interest in the story as a result of the human weaknessesthey embody. Examining the historical story as told in the classroom spacestrangely reveals that this quality is lacking in its characters – the story lacksfigures who have human weaknesses that might tie the students to it. The articlecalls on history teachers to enable these characters to enter the classroom andthus, to intensify the possibility that the students will like their history lessons.